Formulation of Turmeric-Tamarind Jelly Using Psyllium Husk - Yosua Lucky Chandra; Esteria Priyanti (An International Journal Tourism and Community Review, 2024)
The objectives of this study were: 1) to determine the acceptance of color, aroma, texture, and taste of turmeric-tamarind jelly candy with the addition of psyllium husk; and 2) to identify the composition of the selected turmeric-tamarind jelly candy product. The research employed experimental methods, hedonic tests, and ranking tests. Three variants of psyllium husk were used: Product 1 with 1 g, Product 2 with 3 g, and Product 3 with 5 g of psyllium husk added. Data obtained from sensory evaluations were descriptively analyzed using Microsoft Excel 2019. Results indicated that the turmeric-tamarind jelly candy with the addition of 1 g of psyllium husk was the most preferred and well-received product. The composition of the selected jelly candy included 150 ml of turmeric-tamarind extract, 60 g of sugar, 60 g of glucose, 21 g of gelatin, and 1 g of psyllium husk.